PREVALENCE, DETERMINANTS AND CONSEQUENCES OF SPINSTERHOOD IN LAGOS, NIGERIA (2012)
The high prevalence of spinsterhood among urban-based women in Nigeria constitutes a deviation from traditional early marriage pattern. This demographic shift has profound negative consequences on nuptiality, fertility and social status of women. Although the population of spinsters in Nigeria is increasing considerably, negligible attention has been paid to this emerging social reality. This study, therefore, examined the prevalence, determinants and consequences of spinsterhood in Lagos, Nigeria's most urbanised state and home to spinsters of diverse backgrounds. Giddens' Structuration Theory, Walby's Theorising Patriarchy and Barrett and McIntosh's Anti-Social Family perspective provided the theoretical framework for the study. Secondary data from Nigeria's 1991 and 2006 censuses and Demographic and Health Surveys (1990-2008) were used to determine the prevalence of spinsterhood in Lagos and larger Nigerian context. Primary data drawn from twenty-five In-depth Interviews, four Life Histories, and seven Focus Group Discussions with never married women aged 30 and above, were used to determine the predisposing factors, consequences and coping strategies of spinsters. Respondents were selected from diverse ethnic, educational and occupational backgrounds through the snowball technique. Descriptive statistics were used to analyse the secondary data on prevalence. The qualitative primary data on determinants and consequences were content analysed. In the Nigerian context, rate of spinsterhood among women aged 30-85 was 6.7% for the entire nation, and 5.7% in the Southwest geopolitical zone where Lagos is located; whereas the prevalence in Lagos was 7.0%. Prevalence of spinsterhood in Lagos was highest among women aged 30-34 (13.6%) and lowest at 2.5% for women aged 55-59. The most likely group to remain permanently single were women between 45-49 years, and prevalence of spinsterhood among them was 3.1%. Involuntary spinsterhood was predominant (97%) among the respondents. The determinants and consequences of spinsterhood, and coping strategies of spinsters were similar across the diverse ethnic, educational and occupational backgrounds. The major determinant of spinsterhood was drive for economic empowerment and financial independence. Other factors included mate selection preference, negative marital experience of other women, cultural practices, higher education, differences in religious affiliation, urbanisation, and aversion to polygyny. The majority (83%) expressed dissatisfaction with their prolonged spinsterhood. The consequences of spinsterhood included profound stigma, intense pressure to marry, identity crisis, loneliness, fear of permanent singleness and childlessness, among other challenges. The major advantage of spinsterhood was the opportunity to be independent. Coping mechanisms among the spinsters included recourse to religion, friends, supportive family members, devotion to work, and adoption of children. The high prevalence of spinsterhood in Lagos is occasioned by economic, personal and social factors. The phenomenon could become one of the most important components of demographic transition in 21st century Lagos. Social acceptance of spinsterhood as a non-derogatory adult status could help to mitigate its negative effects on spinsters.